CAUSES OF PAIN IN THE MUSCLES OF THE LOWER EXTREMITIES IN CHILDREN WITH CEREBRAL PALSY - Danilov, Oleksandr; Shulga, Oleksandr; Kucheruk, Oleksandr; Bandrina, Kateryna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2024)
A high level of muscle spasticity in children with cerebral palsy is one of the causes of degenerative and dystrophic changes in tissues. Against the background of high spasticity, there is a violation of blood flow in the vessels of the lower extremities, which leads to changes in subfascial pressure and the formation of primary pain syndromes. The analysis of the literature shows the need to study the issues related to the mechanism of formation of changes in the muscles and determine the primary causes of pain. Objective. Тo study the mechanism of changes in the muscles of the lower extremities, as well as the primary causes of pain syndrome. Methods. The analysed indicators were obtained during the treatment of 40 patients with cerebral palsy, who were divided into 3 groups depending on the muscle tone disorder. Clinical and instrumental methods were used to examine patients. The data obtained were statistically processed with the determination of M ± m, the coefficient of reliability according to Student’s criteria. Results. According to the results of the study, high spasticity leads to impaired blood flow and increased subfascial pressure in the musculofascial sheaths. There is an inverse correlation between the increase in subfascial pressure, the diameter of the vessel lumen and blood flow velocity. This is one of the causes of degenerative and denervation changes in muscles and fascia. It was proved that the occurrence of primary pain in the lower extremities is caused by various etiological causes: tissue ischemia; increased subfascial pressure; narrowing of pathologically significant anatomical areas in which nerves lie; degenerative and dystrophic changes in the joints. Conclusions. The study found that the cause of changes in the muscles and fascia is a violation of blood flow, a change in subfascial pressure in the musculofascial cases of the lower extremities. The occurrence of pain in the lower extremities in children with cerebral palsy is multifactorial in nature and consists of myofascial, articular, and tunnel syndromes.